Biosafety education relevant to genetically engineered crops for academic and non-academic stakeholders in East Africa - Sengooba, Theresa; Grumet, Rebecca; Hancock, James; Zawedde, Barbara; Kitandu, Lazaro; Weebadde, Cholani; Karembu, Margaret; Kenya, Eucharia U. (My University, 2009)
Development and deployment of genetically engineered crops requires effective environmental and food safety assessment capacity. In-country expertise is needed to make locally appropriate decisions. In April 2007, biosafety and biotechnology scientists, regulators, educators, and communicators from Kenya, Tanzania, and Uganda, met to examine the status and needs of biosafety training and educational programs in East Africa. Workshop participants emphasized the importance of developing biosafety capacity within their countries and regionally. Key recommendations included identification of key biosafety curricular components for university students; collaboration among institutions and countries; development of informational materials for non-academic stakeholders and media; and organization of study tours for decision makers. It was emphasized that biosafety knowledge is important for all aspects of environmental health, food safety, and human and animal hygiene. Thus, development of biosafety expertise, policies and procedures can be a stepping stone to facilitate improved biosafety for all aspects of society and the environment.
Keywords: biotechnology; environmental safety; Kenya; Tanzania; Uganda